2022
DOI: 10.3390/ijms23042024
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Early Saliva Interaction on Dental Implants and Biomaterials for Oral Regeneration: An Overview

Abstract: The presence of saliva in the oral environment is relevant for several essential health processes. However, the noncontrolled early saliva interaction with biomaterials manufactured for oral rehabilitation may generate alterations in the superficial properties causing negative biological outcomes. Therefore, the present review aimed to provide a compilation of all possible physical–chemical–biological changes caused by the early saliva interaction in dental implants and materials for oral regeneration. Dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Saliva is always present in the oral environment (gingiva, teeth, bone, blood) before any surgical procedure starts. The complexity of saliva interaction control during the placement of oral biomaterials such as dental implants or materials for bone regeneration is challenging, being more demanding in procedures involving more than one professional handling the case [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Saliva is always present in the oral environment (gingiva, teeth, bone, blood) before any surgical procedure starts. The complexity of saliva interaction control during the placement of oral biomaterials such as dental implants or materials for bone regeneration is challenging, being more demanding in procedures involving more than one professional handling the case [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several authors reported different methodologies to collect the saliva and apply it in their studies, even associated with techniques of freezing, filtration or direct application from the subject [ 14 , 31 , 47 , 48 ]. The application of saliva immediately removed from humans showed to be the most similar condition to the clinical environment [ 26 ]; however, it is extremely difficult to perform an entire study with human subjects providing immediate saliva excretion in laboratories without a proper process of storage. Therefore, this investigation was performed on different days, using one day for each surface analysis with a direct saliva collection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, autogenous bone grafts have several drawbacks, such as donor site morbidity, soft tissue and nerve injuries, post-surgery pain, limited harvest quantity, and increased surgical operating time [ 19 , 20 , 21 , 22 , 23 ]. Therefore, the development of alternative scaffolds to autologous bone is necessary [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…It must not be forgotten that a human body, especially the oral cavity, is an aggressive environment containing different ions, enzymes, bacteria, and frequent daily pH changes. Such an environment can cause the release of contaminants from the implant’s surface into surrounding tissues and organs, which can trigger negative biological processes such as allergies or inflammation [ 10 ]. All this clearly underlines the need for improving the production process and introducing regular strict quality controls of implants.…”
Section: Introductionmentioning
confidence: 99%